The commons and anticommons in the reform of property law: An illustration through the new Belgian Civil Code - Sagaert Vincent (Pravni Zapisi)
A property law reform is, in all periods, a most foundational exercise. It determines and translates the (developments in the) relationship of humans with natural resources. This article deals with property law reform in the early 21st century, as it seeks a balance between exclusion and inclusion, the commons and the anticommons, and pursues the protection of sustainability. Apart from other comparative observations, this article takes the new Belgian Civil Code, and especially the property law book, as an example in order to illustrate these developments.